Production Process Analysis to Reduce Defective Products through the Application of Pareto Diagram and The Eight Disciplines Problem Solving Method - Widodo, Dian Setiya; Wahyudi, Pongky Lubas (Heuristic, 2025)
Quality control involves efforts to uphold and enhance product quality in order to align with the specifications established by customers. Employing a combination of the Pareto diagram and the 8D (Eight Disciplines Problem Solving) method represents a robust approach to systematic problem-solving, particularly in manufacturing and quality settings. These two methods can be used together to identify the root causes of problems and then implement effective solutions. This study aims to analyze quality improvement efforts in the production of fiber drum paper as an eco-friendly packaging, focusing on dent defects in the upper body area of the drum, which were found in the crushing and curling process at PT. X. The findings indicated that there were still several defects in the current production process, with the most significant defects occurring in fiber drum paper products. where the dent defect in the upper body area of the drum reached 2%. After improvements were made using the Pareto diagram, Fishbone diagram and the eight disciplines problem-solving method, the dent defect in the upper body area of the drum was successfully reduced to 0.8%, meeting the set improvement targets.